Methods of sustainability assessment of green logistics projects - part I: review of external stakeholders on green logistics initiatives - Toh, Alvin De Rong (Nanyang Technological University, 2022)
Impacts of climate change has been continually felt and worsen over the past century. Upsurge in temperature to date thus far has provoked alterations to both the natural and human systems, including increases in floods, droughts, or some variety of extreme weather such as sea level rise to loss of biodiversity. Green Logistics initiatives have been adopted by many firms to conform to tightening regulation measures and increasing social pressures from various stakeholder community to meet sustainable environmental goals. Like many concepts, Green Logistics is affected by uncertainty stemming from the internal and external environment due to the changing sustainable landscape. Uncertainty is at its peak when involving external variables which Green Logistics initiatives have very little control over. Therefore, this report aims to understand the external environment, namely the external stakeholders in which Green Logistics initiatives operates in. The methodology conducted in this report involves both quantitative and qualitative aspects that are interviews and questionaries with several individuals from industrial players and academics. This is coupled with a comprehensive literature review in the disposition of recognized reports, past research papers and credible news resources from regulatory bodies to assemble distinct viewpoints and a comprehensive understanding of external stakeholders in Green Logistics. This report seeks to investigate the key considerations that the various external stakeholders have when it comes to sustainability in Green Logistics. Furthermore, this report quantifies stakeholder views and its magnitude into a relationship model framework to assess Green Logistics initiatives. In addition, this report further identifies the stakeholder that holds the greatest significance in changing the Green Logistics landscape. This report continues to address existing challenges that Green Logistics initiatives might face during its lifecycle and proposes recommendation guidelines to overcome such problems to achieve long-term sustainability of Green Logistic initiatives